Pulses Based Systems for sustaining soybean in central India - Praharaj, C S; Singh, S S; Jat, Ram Lal; Singh, Ummed; Singh, N P; Elanchezhian, R; Singh, R P (Indian Farming, 2017)
Soybean is undoubtedly a wonder crop. Its productivity level is not keeping a pace with time. Because of both biotic and abiotic stresses, its cultivation is becoming less remunerative in Central India and is less popularized. This needs a fill ups for its possible adoption and spread. The above study concludes on intercropping with pulses/cereal/oilseed that on total system productivity for both kharif + rabi (soybean +intercrop-lentil), significantly higher total productivities and net returns were recorded with soybean + pigeonpea - lentil followed by soybean + urdbean - lentil. Significantly higher productivity was also realized under broad bed over flat planting both during kharif and rabi irrespective of other factors or constraints. Because of scanty rainfall and its uneven distribution, supplementary irrigation once to lentil enhanced its productivity over the rainfed crop.